Enteric pathogen among children under five years old with diarrheal diseases in Indonesia. Issue 1 (November 2021) - Puspandari, N; Amalia, N; Hartoyo, Y; Nursofiah, S; Sunarno, S; Sariadji, K; Soekarso, T; Febrianti, T; Khariri, K; Muna, F; Rizky, A; Saraswati, R D; et al.
Abstract: Diarrheal diseases are the second cause of the high morbidity and mortality in children under five years old. According to the Basic Health Survey 2018 conducted by the Ministry of Health, the prevalence of diarrheal diseases among children under five years old that were diagnosed by healthcare workers was 11.0%. The aim of this study was to describe the enteric pathogen isolated from children with diarrhea. The study was conducted in five cities in Indonesia: Jakarta, Serang, Denpasar, Makassar, and Mataram. The Inclusion criteria were children aged one month to five years old, with diarrhea that was diagnosed by a healthcare worker. The rectal swabs were sent to the Centre for Research and Development for Biomedical and Basic Health Technology, National Institute of Health Research and Development, Ministry of Health in Jakarta. Virus and Enterotoxigenic Escherichia coli (ETEC) identification by using multiplex PCR from Seegene, meanwhile bacteria identified by conventional method. As many as 2626 children under five years old participated in this study. The highest viral pathogen that causes diarrhea is viral 1.807 (68, 81%) and 486 (18, 56%). The virus etiology was Rotavirus 982 (54, 34%) cases, followed by Adenovirus 916 (50.69) cases, Norovirus II 444 (24, 57%) cases, meanwhile the bacteria pathogen were Enterotoxigenic Escherichia coli detected in 262 (9, 98%) followed by Campylobacter jejuni and Shigella spp . This study described Rotavirus is the prevalence etiology of diarrhea among children under five years old followed by Adenovirus and Norovirus, some other cases reported the cause of diarrhea were bacteria ETEC E. coli followed Campylobacter jejuni, Shigella spp, etc.